Small for Size and Flow (SFSF) syndrome: an alternative description for posthepatectomy liver failure - Golriz, Mohammad; Majlesara, Ali; Sakka, Saroa el; Ashrafi, Maryam; Arwin, Jalal; Fard-Rutherford, Nassim; Raisi, Hanna; Edalatpour, Arman; Mehrabi, Arianeb (Clinics and research in hepatology and gastroenterology, 2016)
Small for Size Syndrome (SFSS) syndrome is a recognizable clinical syndrome occurring in the presence of a reduced mass of liver, which is insufficient to maintain normal liver function. A definition has yet to be fully clarified, but it is a common clinical syndrome following partial liver transplantation and extended hepatectomy, which is characterized by postoperative liver dysfunction with prolonged cholestasis and coagulopathy, portal hypertension, and ascites. So far, this syndrome has been discussed with focus on the remnant size of the liver after partial liver transplantation or extended hepatectomy. However, the current viewpoints believe that the excessive flow of portal vein for the volume of the liver parenchyma leads to over-pressure, sinusoidal endothelial damages and haemorrhage. The new hypothesis declares that in both extended hepatectomy and partial liver transplantation, progression of Small for Size Syndrome is not determined only by the “size” of the liver graft or remnant, but by the hemodynamic parameters of the hepatic circulation, especially portal vein flow. Therefore, we suggest the term “Small for Size and Flow (SFSF)” for this syndrome. We believe that it is important for liver surgeons to know the pathogenesis and manifestation of this syndrome to react early enough preventing non-reversible tissue damages.